1997
DOI: 10.2514/2.103
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Placement and Structural Damage Identification from Minimal Sensor Information

Abstract: A method of prioritizing sensor locations on a¯exible structure for the purpose of determining damaged structural elements from measured modal data is presented. This method is useful in applications where practicality dictates only a small subset of the total structural degrees of freedom can be instrumented. In such cases, it is desirable to place sensors in locations yielding the most information about the damaged structure. No a priori knowledge of the damage location is assumed. The prioritization is base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…The literature describes different approaches for sensor placement options, such as prioritizing the sensor location based on a detectability limit [10], using a modal analysis parameter determination for damage localization assessment on a truss structure [11], and by using global search and greedy algorithms [12]. Li et al [13] proposed a sensor optimization algorithm based on maximum energy consumption on sensor candidate location of a civil engineering structure.…”
Section: Introductionmentioning
confidence: 99%
“…The literature describes different approaches for sensor placement options, such as prioritizing the sensor location based on a detectability limit [10], using a modal analysis parameter determination for damage localization assessment on a truss structure [11], and by using global search and greedy algorithms [12]. Li et al [13] proposed a sensor optimization algorithm based on maximum energy consumption on sensor candidate location of a civil engineering structure.…”
Section: Introductionmentioning
confidence: 99%
“…Cobb and Liebst [4] discussed one of the first such approaches. Their sensor placement technique makes no assumption about damage location, but focuses instead on a sensitivity analysis to find the degrees of freedom which maximize the changes due to damage in the observable partial eigenstructure.…”
Section: Nomenclaturementioning
confidence: 99%
“…studied the mode selection strategy in locating damage and concluded that a mode selection based on maximum modal strain energy produced more accurate results than that based on minimum frequency. Cobb and Liebst (1997) proposed the optimal sensor placement for structural damage detection by maximizing system observability. A damage detection method of sensor location optimization, in which the collected information is used, has been presented by Shi et al (2000).…”
Section: Introductionmentioning
confidence: 99%